2021
DOI: 10.3390/ijms22052679
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Methylome Profiling Can Discern Fertility Levels in the Porcine Biomedical Model

Abstract: A combined Genotyping By Sequencing (GBS) and methylated DNA immunoprecipitation (MeDIP) protocol was used to identify—in parallel—genetic variation (Genomic-Wide Association Studies (GWAS) and epigenetic differences of Differentially Methylated Regions (DMR) in the genome of spermatozoa from the porcine animal model. Breeding boars with good semen quality (n = 11) and specific and well-documented differences in fertility (farrowing rate, FR) and prolificacy (litter size, LS) (n = 7) in artificial insemination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 90 publications
1
24
0
Order By: Relevance
“…Differential analyses of the pig sperm transcriptome have shown the relevant associations with sperm quality [189] and fertility [27,190], confirming data in other species [182,[191][192][193][194]. The SP EVs also contain diverse smallRNAs, among which the majority are messenger RNA fragments (mRNA, about 25% of the total reads) followed by piRNAs (15%, almost 20,000), miRNAs (9%, almost 300) and very small amounts of tsRNA (0.01%) [140].…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?supporting
confidence: 70%
See 3 more Smart Citations
“…Differential analyses of the pig sperm transcriptome have shown the relevant associations with sperm quality [189] and fertility [27,190], confirming data in other species [182,[191][192][193][194]. The SP EVs also contain diverse smallRNAs, among which the majority are messenger RNA fragments (mRNA, about 25% of the total reads) followed by piRNAs (15%, almost 20,000), miRNAs (9%, almost 300) and very small amounts of tsRNA (0.01%) [140].…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?supporting
confidence: 70%
“…Such double location reinforces the need of considering the role of EVs as adding material to the spermatozoa yet reminding us of the relevance of proper isolation of the components of semen, so that they can sequenced separately but compared at the same time. Unfortunately, sample sizes are uneven, and semen from boars with well-studied and established fertility must be primarily studied [ 190 ], a shortage nowadays. However, how are these miRNAs affecting fertility?…”
Section: The Particulate Seminal Plasma: the Most Relevant Component Of Seminal Plasma?mentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar biomedical model, boars with high quality semen parameters but lower fertility success have shown that most of the DMRs were hypermethylated on genes related to spermatogenesis, sperm function, fertilization and fertility/prolificacy. Additionally, they showed the same disregulation of sperm miR-153 that occurs in humans, affecting fertilization and embryo rates after IVF [ 129 ].…”
Section: Introductionmentioning
confidence: 99%